On cyclic reduction and finite difference schemes - Zhang, Jun; Kouatchou, Jules; Othman, Mohamed (Elsevier, 2002)
We investigate a family of finite difference schemes for discretizing the two dimensional Poisson equation on both the standard and the reduced grids. We study the relation between the cyclic reduction method and the discretization schemes on different grids. The spectral radii of the Jacobi iteration matrices, and the truncation errors of different discretization schemes are compared analytically and numerically.